2016
DOI: 10.25225/fozo.v65.i3.a8.2016
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of a wide underpass by mammals on an expressway in the Western Carpathians, S Poland

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
1
12
1
Order By: Relevance
“…In our research, wild boars were frequent users of the underpass. This result is in contrast to observations in mountain areas (Mysłajek et al 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In our research, wild boars were frequent users of the underpass. This result is in contrast to observations in mountain areas (Mysłajek et al 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The examined road underpasses were used most intensively in spring and least frequently in winter. The results confirm the observations made by Mysłajek et al (2016), where analogous relationship was reported. Furthermore, it is associated with a reduced tendency of wildlife migration and road crossing in winter (Kämmerle et al 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Currently the study area is crossed by a railway line and a motorway, with limited possibilities for safe crossing by wildlife. Furthermore, the existing underpass is not used by large mammals [54], indicating that they have to cross the transportation network in other locations. This shows that proper planning of road and railroad crossings is needed in the area to avoid the isolation of habitats and limit collision risk for moving animals.…”
Section: Discussionmentioning
confidence: 99%